2019
DOI: 10.1002/chem.201901906
|View full text |Cite
|
Sign up to set email alerts
|

On the Metal Cooperativity in a Dinuclear Copper–Guanidine Complex for Aliphatic C−H Bond Cleavage by Dioxygen

Abstract: Selective oxidation reactionso fo rganic compoundsw ith dioxygenu sing molecular copper complexes are of relevance to syntheticc hemistrya sw ell as enzymatic reactivity.I nt he enzyme peptidylglycine a-hydroxylating monooxygenase (PHM),t he hydroxylating activity towards aliphatic substrates arises from the cooperative effect between two copper atoms, but the detailed mechanism has yet to be fully clarified. Herein, we report on am odel complex showing hydroxylation of an aliphatic ligand initiated by dioxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 118 publications
(157 reference statements)
0
3
0
Order By: Relevance
“…A cupric–superoxide complex with the TMGMP ligand. Adapted with permission from ref . Copyright 2019 Wiley-VCH.…”
Section: N3 or N2 Tridentate Or Bidentate Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cupric–superoxide complex with the TMGMP ligand. Adapted with permission from ref . Copyright 2019 Wiley-VCH.…”
Section: N3 or N2 Tridentate Or Bidentate Ligandsmentioning
confidence: 99%
“…With the ligand derivative H PPMDC, Itoh and co-workers showed that the corresponding cupric superoxide complex [Cu II ( H PPMDC)­(O 2 •– )] + facilitates an aldol-type reaction with carbonyl compound substrates and solvent molecule (acetone) through catalytic C–C bond formation. With the TMG-type ligands (Chart ), Himmel and co-workers also reported a similar aldol reactivity involving a cupric superoxide complex, e.g., [Cu­(TMGMP)­(O 2 •– )] + (Figure ).…”
Section: N3 or N2 Tridentate Or Bidentate Ligandsmentioning
confidence: 99%
“…Examples are entatic state model complexes showing catalytic activity due to charge and electron transfer between the metal center and its ligand sphere. Studies involve the activation of catalytic activity by optically exciting metal complexes and probing them by means of EXAFS and XANES, raising the possibility of studying photoactivated complexes in operando . , The photocatalytic activity of Cu-based metal clusters has been studied through such combinations of optical and X-ray spectroscopies . These studies involved the activation of catalytic activity by optically exciting metal complexes and probing them by means of EXAFS and XANES.…”
Section: Spectroscopies To Investigate Biotransformation Of Nanoparti...mentioning
confidence: 99%
“…31,[34][35][36]38 All exceptions to this side-on O2 binding preference reported, thus far, were obtained using linear tridentate ligands (Chart 1d). [39][40][41][42][43] These Cu II (𝜂 1 -O2 •− ) complexes display a number of common structural and spectroscopic features, but they exhibit very different reactivity properties.…”
Section: Introductionmentioning
confidence: 99%
“…A similar catalytic aldol reaction of acetone was also reported by Himmel and co-workers for their complex [Cu II (𝜂 1 -O2 •− )(TMGMP)] + . 42 In summary, the small range of published 4-coordinate Cu II (𝜂 1 -O2 •− ) complexes display a broad spectrum of reactivity, both electrophilic and nucleophilic in nature, and it is clear that the supporting ligands have a profound influence upon it. The latter complicates efforts to gain insight by comparison with their more numerous and extensively studied 5coordinate Cu II (𝜂 1 -O2 •− ) congeners, as they employ ligands possessing very different donors and topological profiles.…”
Section: Introductionmentioning
confidence: 99%